Radiofrequency energy in surgery: state of the art - Ihnát, Peter; Ihnát Rudinská, Lucia; Zonča, Pavel (Surgery today, 2014)
Over a period of more than 100 years, radiofrequency energy has been introduced in many fields and applications in medicine. At present, radiofrequency constitutes the basis of numerous medical devices employed in almost all medical specialties. It is particularly applicable and valuable in various minimally invasive procedures for its locally focused effects. Radiofrequency energy is a technical term established to describe high-frequency alternating electrical currents (with a frequency ranging from 300 kHz to 3 MHz) and their impact on biological tissue. The application of RF energy causes controlled tissue heating with consequent cell protein denaturation and desiccation, which leads to cell death and tissue destruction. The primary principle of radiofrequency is that the generated heat can be used to cut, coagulate or induce metabolic processes in the target tissue. The authors of this paper offer a comprehensive and compact review of the definition, history, physics, biological principles and applications of radiofrequency energy in current surgery.
Keywords: Biophysical Phenomena; databáze bibliografické; nádory; biofyzikální jevy; varixy; hepatektomie; Varicose Veins; Hepatectomy; Catheter Ablation; Databases, Bibliographic; miniinvazivní chirurgické výkony; Neoplasms; Minimally Invasive Surgical Procedures; katetrizační ablace